ANALYSIS OF THE RELATIONSHIP OF KNOWLEDGE, ATTITUDE, AND AVAILABILITY OF FACILITIES WITH WASTE MANAGEMENT ACTIONS IN THE BAJO COMMUNITY IN THE COASTAL AREA, WANGKOLABU VILLAGE, TOWEA DISTRICT, MUNA REGENCY IN 2022 - Wa Insa Insa; Ramadhan Tosepu Ramadhan Tosepu; Nurmaladewi Nurmaladewi (Pengurus Daerah Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI) Sulawesi Tenggara, 2022)
The waste problem is a problem that is closely related to humans and can be encountered in everyday life, both in individual life and in the environment. However, the problem that we often encounter in coastal communities is that there are still many of them who throw garbage in any place, including throwing it at sea. This study aims to determine the relationship between knowledge, attitudes, and availability of facilities with waste management actions in the coastal community of Wangkolabu Village, Towea District, Muna Regency. The research method used is analytic observational research design with cross sectional study. The population in this study was the entire community of Wangkolabu Village, amounting to 345 families with a sample of 93 respondents. The results showed that there was no relationship between knowledge and waste management actions (p value = 0.344), there was a relationship between attitudes towards waste management actions (p value = 0.032), and there was a relationship between the availability of facilities and waste management actions (p value = 0.011). The conclusion shows that there is no relationship between the knowledge variable and the waste management action, then there is a relationship between the attitude variable and the availability of facilities for the waste management action.